2016
DOI: 10.1364/optica.3.000407
|View full text |Cite
|
Sign up to set email alerts
|

Chip-to-chip quantum photonic interconnect by path-polarization interconversion

Abstract: Integrated photonics has enabled much progress towards quantum technologies. Many applications, e.g., quantum communication, sensing, and distributed cloud quantum computing, require coherent photonic interconnection between separate on--chip subsystems. Large--scale quantum computing architectures and systems may ultimately require quantum interconnects to enable scaling beyond the limits of a single wafer, and towards multi--chip systems. However, coherently connecting separate chips remains a challenge, due… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 62 publications
2
115
0
1
Order By: Relevance
“…Entangled path-encoded qubits can be generated by coherently pumping two spontaneous parametric down conversion (28,29) or spontaneous four-wave mixing (SFWM) photon-pair sources (30,31). The approach can be generalized to qudits via the generation of photons entangled over d spatial modes by coherently pumping d sources (28,32).…”
Section: Large-scale Integrated Quantum Photonic Circuitmentioning
confidence: 99%
“…Entangled path-encoded qubits can be generated by coherently pumping two spontaneous parametric down conversion (28,29) or spontaneous four-wave mixing (SFWM) photon-pair sources (30,31). The approach can be generalized to qudits via the generation of photons entangled over d spatial modes by coherently pumping d sources (28,32).…”
Section: Large-scale Integrated Quantum Photonic Circuitmentioning
confidence: 99%
“…It is also demonstrated that the introduction of active (gain) media inside the plasmonic ENZ nanochannels can lead to perfect loss compensation of the inherent 28 (nonradiative) plasmonic losses that, subsequently, reduces decoherence and further boosts transient quantum entanglement. We envision that the presented passive and active ENZ mediated RET and entangled states will find applications in future quantum information and communications integrated systems on a chip [58,59], the design of new low-threshold subwavelength nanolasers [60], and the creation of ultrasensitive quantum metrology devices [61]. Hence, effective ENZ waveguide media have the potential to become crucial components to the emerging field of quantum plasmonics [9].…”
Section: Discussionmentioning
confidence: 99%
“…The photon pairs are finally sent to the part of quantum state analyzer to measure the property of path entanglement. The analyzer consists of two balanced MZIs, which can realize the  z R and  y R rotations on the signal/idler photons [23,29]. At the outputs of the MZIs, four grating couplers are used to couple the photons to optical fibers.…”
Section: ( )mentioning
confidence: 99%